MEKANISME KERJA ANDROGRAFOLIDA DARI SAMBILOTO SEBAGAI SENYAWA ANTIOKSIDAN - Elvira Yunita (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2021)
Andrographolide is the main bioactive compound derived from sambiloto, Andrographis paniculata. Andrographolide compounds can potentially be used as phytopharmaca substances. Andrographolide has very broad pharmacological aspects, including anti-inflammatory, anticancer and anti-diabetic. The pharmacological aspects possessed by andrographolide are probably closely related to the chemical profile and the mechanism of action of andrographolide as an antioxidant in counteracting free radicals. Therefore, it is important to know the chemical profile and mechanism of action of andrographolide compounds as antioxidants to understand the mechanism of action of these compounds in dealing with various diseases. This study is based on a review of related literature. Based on the literature review, it was found that the mechanism of action of andrographolide as anti-cancer, anti-inflammatory and anti-dyslipidemia is closely related to the mechanism of action of this compound as an antioxidant. The unsaturated γ- lactone structure at C13 and C14 of andrographolide can neutralize superoxide anions. The double bond in this carbonyl ester group will affect the deprotonization of the H atone located at C15 so that the H atoms on C15 will be easily extracted by the highly reactive superoxide anion. Thus, andrographolide can stop the chain reaction of a radical molecule. This mechanism can cause andrographolide compounds to play a role in reducing the effects of free radicals in various diseases.